Non-membrane optical microphone based on longitudinal modes competition - Pua, Chang Hong; Norizan, Siti Fatimah; Harun, Sulaiman Wadi; Ahmad, Harith (Elsevier, 2011)
We propose and demonstrate a simple and cost effective non-membrane optical microphone (OM) consisting of only a standard erbium doped fibre amplifier (EDFA) and a 25 km of conventional single mode fibre (SMF) as the sensing medium. A photo detector is used for data acquisition. The proposed setup utilizes the disturbances in the competing longitudinal modes in a low reflectivity fibre resonator whereby airborne acoustic waves impacting the surface of the fibre will modulate the intensity of the optical signal in the fibre. This modulation frequency is analyzed using the fast fourier transform (FFT) technique to extract the information embedded in the optical signal. The experiment shows that the system is capable of picking up the airborne acoustic waves and can find many potential applications.